A systematic review of quantitative studies concerning psychological aspects of early specialisation - Downing, C.; Redelius, K.; Nordin-Bates, S. (International Journal of Sport and Exercise Psychology, 2024)
Despite the intense and long-standing interest surrounding early sport specialisation, scholars still debate its nature and implications. Previous researchers have also identified the need for further research relating to the psychological aspects of early specialisation such as lower quality motivation, dropout and burnout. To help guide future research it is important to build upon the quantitative literature concerning such psychological aspects of early specialisation. The specific aims of this paper are to provide an overview of research results of quantitative studies that set out to explore relationships between early specialisation and psychological aspects, and to critically examine the designs of such studies. As such, study design characteristics including participant demographics, the psychological aspects represented, and the research questions and results are explored. Data searches were conducted in PubMed, SportDiscus, and PsychINFO using search terms such as "early sport speciali*". Twenty-one relevant papers met the inclusion criteria. The results highlight that the published papers in this area are broad in some respects (variety of sports, performance levels, and gender), but narrow in others (North American dominance, few psychological aspects explored, and few papers per psychological aspect). Many of the studies are based on cross-sectional and retrospective self-reports. Overall, this paper serves as a foundation on which to design future research studies in this area.